Spiral - Gordon, Roderick; Williams, Brian (New York : Chicken House/Scholastic, 2012)
When an evil predatory race emerges from dormancy to infest London and uses human victims to increase their population, Will, a member of a heavily armed crew of weary renegades and cynical ex-soldiers, becomes an unwitting world defender.
Keywords: England -- Fiction; Science fiction; Adventure fiction